Immunopathogenesis of Hepatitis E Virus Infection - Wedemeyer, Heiner; Rybczynska, Jolanta; Pischke, Sven; Krawczynski, Kris (Seminars in Liver Disease, 2013)
The course of hepatitis E virus infection (HEV) can vary substantially between different individuals. Although most infections take a clinically silent asymptomatic course, a few patients may develop severe hepatitis that can progress to fulminant hepatic failure. In addition, cases of chronic hepatitis E have been described in immunosuppressed patients. The detailed mechanisms leading to different clinical outcomes of HEV infection are only partially understood. Both viral factors including the HEV genotype and the dose of the infectious inoculum, as well as host factors such as stage of liver disease, pregnancy or distinct genetic polymorphisms determine the course of HEV infection. Recent studies were able to associate T-cell responses, activation of the interferon system and viral evolution with severity or chronicity of hepatitis E. We here summarize the emerging data on the immunopathogenesis of HEV infection.
Keywords: hepatitis E virus; HEV; T-cell responses; humoral immunity; animal models